Intracellular forms of simian virus 40 nucleoprotein complexes. II. Biochemical and electron microscopic analysis of simian virus 40 virion assembly. - Coca-Prados, M (1979)
The simian virus 40 virion assembly process was studied with pulse-labeling kinetics of virion proteins, CsCl gradient analysis, electron microscopy, and low-salt gel electrophoresis. The results obtained are consistent with the model of gradual addition and organization of capsid proteins around simian virus 40 chromatin. Empty virions, as observed in the CsCl gradient by previous workers, were found to be the dissociation product of immature virus. Histone H1 was found in simian virus 40 chromatin and virion assembly intermediates but not in the mature virion banding at 1.34 g/ml in the CsCl gradient.